A half-way right: free education, indirect costs, and educational policy - Fernández Enguita, Mariano (Avances en Supervisión Educativa, 2014)
This paper examines those indirect costs of education associated to state funded schooling that come to be privately financed by families, specially those linked to mandatory or mandated provision schooling. Discussion is more detailed about textbooks, school meals and academic support activities. Then we study the consequences of this private spending for gratuity and its effects related to educational and social equality or inequality. Finally, we analyze the implications related to sectional interests at stake and educational policies.